PELATIHAN PLIOMETRIK DIAGONAL CONE HOP LEBIH EFEKTIF DIBANDINGKAN FRONT CONE HOP UNTUK MENINGKATKAN KEKUATAN OTOT TUNGKAI DAN KECEPATAN TENDANGAN PADA PEMAIN SEPAK BOLA SMK SMSR UBUD - I Made Dwi Ariyuda; I Wayan Weta; I Made Muliarta; Ketut Tirtayasa; I Made Jawi; Putu Adiartha Griadhi (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2018)
The performance of soccer branch at SMK SMSR Ubud has not shown maximum result. To increase the performance of soccer branch, it was done by plyometric diagonal cone hop training and front cone hop. This research aim to know that plyometric diagonal cone hop training and front cone hop is to increase leg muscle strength and kick velocity, and plyometric diagonal cone hop training is more effective than front cone hop to increase leg muscle strength and kick velocity. The research method is experimental method The Randomized Pre and Post Test Group Design. The samples of research are 30 soccer players at SMK SMSR Ubud and divided into 2 (two) groups. The first group was handled with Plyometric diagonal cone hop training, and the second group was handled with Plyometric front cone hop training. The frequencies of training are 3 times in a week for 6 weeks. Leg muscle strength measured by leg dynamometer and kick velocity measured by meter indicator and video recording. The result of the intergroup t-paired test of this research for the first group before and after training that leg muscle mean is 97,80 ± 19,91 and 140,1 ± 10,01 kgs and kick velocity is 13,21 ± 2,16 and after training 21,86 ± 4,88 m/s with (p< 0,01). While the result for the second group before and after training that leg muscle mean is 98,00 ± 14,56 and after training 126 ± 12,7 kgs and kick velocity is 11,18 ± 1,59 and after training 16,18 ± 2,48 m/s with (p<0,01). Results of increased leg muscle strength and kick velocity between both of groups before and after training tested by independent t-test with p=0,002 & p<0,01 that is means there are significant differentiation. The conclusion is both of this training can be used to increase leg muscle strength and kick velocity. But, Plyometric diagonal cone hop is more effective than front cone hop to increase leg muscle strength and kick velocity.